2011
DOI: 10.5539/jsd.v4n6p36
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sustainability Assessment and Sustainability/Environmental Rating Systems and Credit Weighting Tools

Abstract: Developing a new assessment tool in the area of sustainable development requires a strategic methodology for a cohesive and logical framework incorporating relevant theory and practical experience, building on a critical analysis of the state of the art. The assessment process implies the existence of tools, instruments, processes, and methodologies to measure performance in a consistent manner with respect to pre-established standards, guidelines, factors, or other criteria. Sustainability assessment practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 34 publications
0
81
0
8
Order By: Relevance
“…The common tendency has been to establish an objective and comprehensive methodology for assessing a broad range of environmental impacts caused by a building or even a group of buildings. The purpose of these schemes is to measure the environmental sustainability of a built environment in a consistent and comparable manner, with respect to pre-established standards, guidelines, factors, or criteria [18]. The two main approaches that have been used to design environmental assessment schemes for buildings are life cycle assessment (LCA) and building assessment methods or rating systems.…”
Section: Overview Of Environmental Assessment Schemes For Buildingsmentioning
confidence: 99%
“…The common tendency has been to establish an objective and comprehensive methodology for assessing a broad range of environmental impacts caused by a building or even a group of buildings. The purpose of these schemes is to measure the environmental sustainability of a built environment in a consistent and comparable manner, with respect to pre-established standards, guidelines, factors, or criteria [18]. The two main approaches that have been used to design environmental assessment schemes for buildings are life cycle assessment (LCA) and building assessment methods or rating systems.…”
Section: Overview Of Environmental Assessment Schemes For Buildingsmentioning
confidence: 99%
“…The AHP approach has been widely adopted in the built environment fields as decision-making tool [25], [34]- [36]. Existing performance schemes and rating tools such as LEED, BHHI and BSCI also adopted the process of AHP to develop hierarchy or rating tool [35], [37]. It is also found that AHP is used to assess risk in a supply chain [38].…”
Section: Application Of Analytical Hierarchy Processmentioning
confidence: 99%
“…To overcome this problem, the UN Commission on Sustainable Development (UNCSD 1997) attempted to formulate a new Driving Forces-State-Response (DSR) framework, which includes not only the social, political, economic, and demographic pressures in the PSR model, but also pressures that result from the natural system. While the former PSR model only focused on the anthropogenic pressure and response, the DPSIR model is more comprehensive and incorporates natural driving forces (Bowen and Riley 2003;Poveda and Lipsett 2011). Environmental management studies often adopt a DPSIR-based model to analyse factors behind the problem being addressed for specific policy options (Jorge et al 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%